ASSOCIATION OF FOOT AND MOUTH DISEASE VACCINATION WITH FERTILITY PERFORMANCE OF BALI CATTLE ON FARMERS IN BADUNG DISTRICT - Ni Luh Putu Ditha Rysdayeni; I Ketut Puja; I Wayan Sukernayasa (Fakultas Kedokteran Hewan Universitas Udayana, 2025)
Foot and mouth disease remains one of the most economically important infectious diseases in production animals. This disease can have many consequences, including reduced productivity, limited market access, and loss of livestock herds. Foot and Mouth Disease (FMD) vaccination is a crucial preventive measure to maintain livestock health, but its impact on the fertility performance of Bali cattle requires further investigation. This study aimed to analyze the association between FMD vaccination and the fertility performance of Bali cattle in Badung Regency. The study was conducted on 390 vaccinated Bali cattle, with fertility parameters observed including abortion, retained placenta, and repeat breeding rates. The results showed an abortion rate of 6.4% and a repeat breeding rate of 34.4%. Statistical analysis using the Test of Between-Subject Effects revealed a significance value of P<0.05, indicating a significant association between FMD vaccination and the fertility performance of Bali cattle. These findings provide important insights into reproductive management and highlight the need to consider vaccination aspects in cattle husbandry programs.